Inf-Convolution and Regularization of Convex Functions on Riemannian Manifolds of Nonpositive Curvature - Azagra, Daniel; Ferrera, Juan (Revista Matemática Complutense, 2006)
We show how an operation of inf-convolution can be used to approximate convex functions with C1 smooth convex functions on Riemannian manifolds with nonpositive curvature (in a manner that not only is explicit but also preserves some other properties of the original functions, such as ordering, symmetries, infima and sets of minimizers), and we give some applications.